1985
DOI: 10.1002/j.1460-2075.1985.tb04055.x
|View full text |Cite
|
Sign up to set email alerts
|

The common 90-kd protein component of non-transformed ‘8S’ steroid receptors is a heat-shock protein.

Abstract: Non‐transformed steroid receptors have an approximately 8S sedimentation coefficient that corresponds to an oligomeric structure of 250‐300 kd which includes a non‐hormone binding 90‐kd protein. A monoclonal antibody BF4 raised against the purified, molybdate‐stabilized, 8S progesterone receptor (8S‐PR) from chick oviduct, recognizes 8S forms of all steroid hormone receptors. BF4 was found specific for a 90‐kd protein present in great abundance in all chicken tissues, including that present in 8S‐forms of ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
140
0
4

Year Published

1986
1986
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 516 publications
(149 citation statements)
references
References 33 publications
(18 reference statements)
5
140
0
4
Order By: Relevance
“…A comparison of the HSP90 and kinaseassociated P90 by proteolytic digestion indicated the two were identical and this was confirmed when the P90 showed a positive response to our antibodies specific to the HSP90 (57). These results set the stage for the more recent revelations that HSP90 also forms a complex with steroid receptors (7,66,69). Both the receptor and kinase undergo intracellular translocations; in one case from cytoplasm to the nucleus and in the other (the kinase), from polysome to the cell's plasma membrane.…”
Section: Approaches To the Problemmentioning
confidence: 77%
“…A comparison of the HSP90 and kinaseassociated P90 by proteolytic digestion indicated the two were identical and this was confirmed when the P90 showed a positive response to our antibodies specific to the HSP90 (57). These results set the stage for the more recent revelations that HSP90 also forms a complex with steroid receptors (7,66,69). Both the receptor and kinase undergo intracellular translocations; in one case from cytoplasm to the nucleus and in the other (the kinase), from polysome to the cell's plasma membrane.…”
Section: Approaches To the Problemmentioning
confidence: 77%
“…Among the heat-shock proteins, HSP90 is a cytoplasmic protein in unstressed cells. It has been shown that HSPBO is associated with steroid hormone receptors and regulates their activation mechanisms [2]. However, the physiological roles of heat shock proteins including HSP90 still remain to be elucidated.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…It contains only one hormone-binding potypeptide of Mr -I00000 per complex [7,8]. We now know that the heat shock protein hsp90 is a constituent of the heteromeric gtucocorticoid receptor structure [4,6,9,10]: it may be present as Abbreviations: DMS, dimethyl suberimidate; nt i, receptor of 'increased nuclear transfer'; PAGE, polyacrylamide gel electrophoresis a dimer [5,11,12]. The involvement of other molecular components is less clear.…”
Section: Introductionmentioning
confidence: 99%